Genomic comparison of chitinolytic enzyme systems from terrestrial and aquatic bacteria. (15th July 2014) - Bai, Yani; Eijsink, Vincent G. H.; Kielak, Anna M.; van Veen, Johannes A.; de Boer, Wietse
Summary: Chitin degradation ability is known for many aquatic and terrestrial bacterial species. However, differences in the composition of chitin resources between aquatic (mainly exoskeletons of crustaceans) and terrestrial (mainly fungal cell walls) habitats may have resulted in adaptation of chitinolytic enzyme systems to the prevalent resources. We screened publicly available terrestrial and aquatic chitinase‐containing bacterial genomes for possible differences in the composition of their chitinolytic enzyme systems. The results show significant differences between terrestrial and aquatic bacterial genomes in the modular composition of chitinases (i.e. presence of different types of carbohydrate binding modules). Terrestrial A ctinobacteria appear to be best adapted to use a wide variety of chitin resources as they have the highest number of chitinase genes, the highest diversity of associated carbohydrate‐binding modules and the highest number of CBM33‐type lytic polysaccharide monooxygenases. A ctinobacteria do also have the highest fraction of genomes containing β‐1, 3‐glucanases, enzymes that may reinforce the potential for degrading fungal cell walls. The fraction of bacterial chitinase‐containing genomes encoding polyketide synthases was much higher for terrestrial bacteria than for aquatic ones supporting the idea that the combined production of antibiotics and cell‐wall degrading chitinases can be an important strategy in antagonistic interactions with fungi.